2007
DOI: 10.1124/mol.107.039040
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, Calcium, and Calpain are Key Mediators of Resveratrol-Induced Apoptosis in Breast Cancer

Abstract: Resveratrol (RES), a natural plant polyphenol, has gained interest as a nontoxic chemopreventive agent capable of inducing tumor cell death in a variety of cancer types. However, the early molecular mechanisms of RES-induced apoptosis are not well defined. Using the human breast cancer cell lines MDA-MB-231 and MCF-7, we demonstrate that RES is antiproliferative and induces apoptosis in a concentration-and time-dependent manner. Preceding apoptosis, RES instigates a rapid dissipation of mitochondrial membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 36 publications
8
151
2
Order By: Relevance
“…Further, CaSR knockdown decreases proliferation and bone metastasis of prostate cancer cells (59). In contrast to the aforementioned findings, other studies have reported a role for rise in cytosolic Ca 2ϩ levels in cancer cell apoptosis (88). Sareen et al (88) showed that resveratrol induces breast cancer cell apoptosis via Ca 2ϩ -dependent activation of calpain protease.…”
mentioning
confidence: 42%
“…Further, CaSR knockdown decreases proliferation and bone metastasis of prostate cancer cells (59). In contrast to the aforementioned findings, other studies have reported a role for rise in cytosolic Ca 2ϩ levels in cancer cell apoptosis (88). Sareen et al (88) showed that resveratrol induces breast cancer cell apoptosis via Ca 2ϩ -dependent activation of calpain protease.…”
mentioning
confidence: 42%
“…Recently it has been shown with the help of live cell microscopy that resveratrol causes an early biphasic increase in the concentration of free intracellular calcium [(Ca +2 )i] levels, which may result from the depletion of the endoplasmic reticulum stores in breast cancer cells. 34 The apoptosis is mediated by a mitochondrial-dependent pathway and calpain, a Ca +2 regulated protein, which also plays a role in the resveratrol-mediated apoptosis in MCF-7 cells. 34 Tang et al 35 reported that resveratrol induces nuclear accumulation of COX-2 protein in human breast cancer MCF-7 and MDA-MB-231 cell cultures, a process dependent on MAPK ½, and AP-1 eventually results in a p53-mediated apoptosis.…”
Section: Breast Cancermentioning
confidence: 99%
“…34 The apoptosis is mediated by a mitochondrial-dependent pathway and calpain, a Ca +2 regulated protein, which also plays a role in the resveratrol-mediated apoptosis in MCF-7 cells. 34 Tang et al 35 reported that resveratrol induces nuclear accumulation of COX-2 protein in human breast cancer MCF-7 and MDA-MB-231 cell cultures, a process dependent on MAPK ½, and AP-1 eventually results in a p53-mediated apoptosis. The compound also decreases the telomerase activity in vitro.…”
Section: Breast Cancermentioning
confidence: 99%
“…Other cytosolic cysteine proteases, known as calpain I and calpain II, require intracellular calcium (Ca 2+ ) for activation, and may trigger apoptosis and necrosis through the proteolysis of cellular substrates, including cytoskeletal and membrane proteins (17)(18)(19). Calpains can also activate proapoptotic Bcl-2 family members, resulting in outer mitochondrial membrane permeabilization and the release of proapoptotic proteins into the cytosol (see refs.…”
Section: Introductionmentioning
confidence: 99%